BODIES THAT EDUCATE, BODIES THAT SUFFER: INTERSECTIONALITY OF GENDER, RACE, AND CLASS IN HEALTH EDUCATION - Evangelista de Sousa, Jackeline; Ricardo de Lima Santos, Lauro; Moisés de Lima Júnior, Erivar; Rodrigues da Silva, Mônica; Jandira Rodrigues da Silva, Maria (Revista Gênero e Interdisciplinaridade, 2026)
The training of health professionals, historically based on universalist models, has shown limitations in understanding the inequalities that shape health, illness, and care processes. In this context, the perspective of intersectionality of gender, race, and class emerges as a fundamental theoretical-analytical tool for critically analyzing these dynamics. This study aimed to analyze how social markers of difference influence health education, with emphasis on subject constitution and implications for professional practice. This is a theoretical-reflective study based on a critical analysis of scientific literature. The findings indicate that the lack of an intersectional approach in academic curricula contributes to the reproduction of care practices that disregard individuals’ specificities, reinforcing structural inequalities. Gender, race, and class operate in an interconnected way, producing differentiated experiences of vulnerability and access to health services. Furthermore, the centrality of the body as a territory of experiences and inequalities is highlighted, showing that individuals in training are shaped by power relations that impact their trajectories. It is concluded that incorporating intersectionality into health education represents an ethical and political commitment to equity, being essential for the development of more critical, inclusive, and human rights-oriented professional practices.